2001
DOI: 10.1128/iai.69.8.5193-5197.2001
|View full text |Cite
|
Sign up to set email alerts
|

Toxin Levels in Serum Correlate with the Development of Staphylococcal Scalded Skin Syndrome in a Murine Model

Abstract: Staphylococcal scalded skin syndrome (SSSS) is an exfoliative dermatitis that results from infection with exfoliative toxin-producing Staphylococcus aureus. SSSS is seen primarily in infants and children. Here we ask if there is a specific maturation process that protects healthy adults from this syndrome. For these studies, an active recombinant exfoliative toxin A (rETA) was used in a neonatal mouse model. A time course generated on the susceptibility to the toxin as a function of mouse age indicated that BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Relatively low antibody titres, as generally seen in premature infants, are mentioned in the literature as potential contributing factors [12,13]. In the light of a more recent publication, immature clearance of the toxin from the bloodstream seems to be a much more likely explanation for this occurrence [15]. This entity in its generalised form is the most severe manifestation of all S. aureus associated skin diseases.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Relatively low antibody titres, as generally seen in premature infants, are mentioned in the literature as potential contributing factors [12,13]. In the light of a more recent publication, immature clearance of the toxin from the bloodstream seems to be a much more likely explanation for this occurrence [15]. This entity in its generalised form is the most severe manifestation of all S. aureus associated skin diseases.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of ETA was confirmed by Western blot analysis using anti-ETA polyclonal antiserum. Toxin activity was confirmed by injection of 10 ll of the partially purified culture supernantant into the subcutaneous tissue at the nape of the neck of newborn Balb/c mice as described [14,15]. The mice were placed back with lactating mothers and were observed at 4 h post-injection for signs of exfoliation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This link between ETB and generalized SSSS might be due to increased virulence of ETB or to more abundant ETB release. Plano et al recently demonstrated in an experimental model that high ET serum concentrations were associated with generalized SSSS (21). Differential passage of ETA and ETB through the epithelium could also contribute to this link between ETB and generalized SSSS.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, it is important to distinguish between streptococci and staphylococci for diagnosis and further to deter- To date, PCR-assisted detection of epidermolysin-encoding genes has been reported only after isolation of staphylococci (3,4,14,17). Injected epidermolysins have been shown to persist in serum in mice (25), as have epidermolysin-producing isolates from patients with atopic dermatitis (29). The ability to detect these toxins directly in bulla fluids and possibly in sera might be of interest.…”
Section: Discussionmentioning
confidence: 99%